Making sport history
1 online resource (xvii, 244 pages)
Keywords: "How does the historian's approach to the history of sport differ from those trained in the social sciences or in physical education? All three have contributed significantly to the remarkable amount of research in sports history in the last generation. But what is the relationship between them? Why, in particular, have historians become interested in sport? Which topics have historians chosen to study in sports history? How has their work influenced the wider world of history and been influenced by it? This important new collection of work by some of the world's leading sport historians seeks to answer these questions and more, offering a fascinating overview of the evolution, current condition and future prospects of the discipline of sport history"--